The Influence of Islamic Financial Literacy and Islamic Banking Product Perceptions on Investment Behavior: Evidence of Religiosity as a Moderating Variable - Permata Andini Sinaga; Yulfiswandi Yulfiswandi (Transpublika Publisher, 2026)
Backgrounds: Although sharia finance is developing rapidly, optimal investment practices in this sector are very limited, especially in developing countries. Objectives: This study examines the impact of sharia financial literacy and perception of sharia banking products on investment decisions, while also exploring the role of religious moderation. Methodology: By using quantitative methodology, data was collected from 561 participants with prior experience or expressed interest in Sharia financial services were recruited through an online questionnaire. Direct effects and moderating relationships were assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The results show that the understanding of Islamic finance and the perception of Islamic banking products significantly increases investment decision-making. On the other hand, religiosity does not show a significant direct impact on investment behavior. Further analysis reveals that although religiosm does not modify the impact of financial literacy on investment choices, religiosity significantly weakens the relationship between perceptions of sharia banking products and investment behavior. Conclusions: In aggregate, cognitive and perceptual antecedents are shown to predominate over piety in configuring Sharia-compliant investment behavior. The present study substantiates the contingent function of religiosity, delineates pragmatic implications for the Sharia financial industry, and articulates informed directions for future praxis.